The Internalization of Democratic Values Through Social Studies Learning at MA Islamiyah Senori Tuban - Rifai; Anggraeni Ratridite Sudarso; Deni Pratiwi (International Journal of Interdisciplinary Research, 2025)
This study investigates the internalization of democratic values through Social Studies learning at MA Islamiyah Senori Tuban. Education serves as a key mechanism for developing civic responsibility, critical thinking, and participatory attitudes among students. A qualitative case study design was employed to explore classroom practices and student experiences in an Islamic educational context. Data were collected through in-depth interviews and classroom observations involving teachers, students, and school stakeholders. The analysis reveals that democratic values such as tolerance, responsibility, and active participation are fostered through interactive learning strategies, including group discussions, collaborative projects, and election simulations. Students demonstrate increased engagement, confidence, and awareness of democratic processes when involved in experiential activities. Variations in participation levels and difficulties in understanding abstract civic concepts remain evident among some students. Institutional support, teacher competence, and resource availability influence the effectiveness of implementation. The findings indicate that participatory learning environments strengthen democratic character formation and provide meaningful learning experiences. The study contributes to the understanding of how democratic and religious values can be integrated within Social Studies education.